Third International Congress on Information and Communication Technology ICICT 2018, London - Yang, Xin-She; Sherratt, Simon; Dey, Nilanjan; Joshi, Amit (Advances in Intelligent Systems and Computing, 2019)
The book includes selected high-quality research papers presented at the Third International Congress on Information and Communication Technology held at Brunel University, London on February 27-28, 2018. It discusses emerging topics pertaining to information and communication technology (ICT) for managerial applications, e-governance, e-agriculture, e-education and computing technologies, the Internet of Things (IOT), and e-mining. Written by experts and researchers working on ICT, the book is suitable for new researchers involved in advanced studies.